Creating materials with a desired refraction coefficient: numerical experiments. - Indratno, Sapto W.; Ramm, Alexander G. (My University, 2010)
A recipe for creating materials with a desired refraction coefficient is implemented numerically. An error estimate is given for the approximate solution of the many-body scattering problem in the case of small scatterers. This result is used for the estimate of the minimal number of small particles to be embedded in a given domain D in order to get a material whose refraction coefficient approximates the desired one with the relative error not exceeding a desired small quantity.
Keywords: many-body wave scattering problems; metamaterials; refraction coefficient